COMPARATIVE CHARACTERISTICS AND RESULTS OF SURGICAL TREATMENT IN PATIENTS WITH MEDIAN ARCUATE LIGAMENT SYNDROME IN COMBINATION WITH REFLUX ESOPHAGITIS - A. M. Ignashov; Zhuo Wang; S. G. Balandov; D. V. Kachalov; E. V. Blinov; M. V. Mamchenkova; A. Yu. Gichkin; A. N. Morozov; L. F. Kovaleva; S. D. Migashchuk (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Relevance. Clarifying the sequence and mutual connection of the median arcuate ligamentum syndrome (MALS) and reflux esophagitis (RE) makes it possible to determine the indications and success of the operation. The objective of the study was to compare the results of the examination and operations in patients with the MALS in combination with RE. Material and methods. 198 patients with MALS were examined and operated. Among them, 85 patients was just with MALS, and decompression of celiac trunk was performed for them. 84 patients had MALS and RE, simultaneously decompression of celiac trunk and Nissen fundoplication were performed for that group of patients. 29 patients had MALS and RE, only decompression of celiac trunk was performed for that group. A comparative analysis of the results of examination and surgical treatment of 85 patients with the MALS and 84 in combination with RE was carried out. The average age of the patients is about 30 years, the female gender prevailed. The feeling of heaviness and abdominal pain due to eating and physical activity, neurovegetative disorders was almost in all patients. Daily or weekly heartburn, regurgitation, vomiting and dysphagia as well as edema, erythema and erosion of the esophageal mucosa were observed mainly in patients with MALS in combination with ER. Results. Significant compression stenosis of the celiac trunk was detected in all patients. After the decompression of the celiac trunk in patients with MALS as well as decompression of the celiac trunk and Nissen fundoplication in patients with MALS in combination with ER, most of them received good clinical results and normalization of anatomical and hemodynamic parameters in celiac trunk. Conclusion. In the combined version of the MALS and RE and the corresponding indications it is expedient to perform decompression of celiac trunk and Nissen fundoplication simultaneously.